Precarious Planning of Translations into the Ukrainian at the Turn of the 1930s in the Context of the Soviet Canon Formation of Translated Literature - Kolomiyets, Lada (East/West, 2023)
Based on an analysis of archival documents, this paper illuminates a part of Ukrainian history with which anglophone readers may be unfamiliar. This study, overall, makes the case that translation is in fact an integral part of Ukrainian cultural history, not merely an addition to it. This paper examines the typescripts of three lists of foreign literary works recommended for translation and publication in the early 1930s that the author recently found in the archives of the Hryhorii Kochur Literary Museum in Irpin: “Spysok tvoriv chuzhozemnykh literatur, shcho ïkh bazhano pereklasty v pershu cherhu” (“A List of Works of Foreign Literature That Should Be Translated First”) along with its introductory note “Do sektora ‘Literatury i Mystetstva’” (“To the Literature and Art Section”); “Literaturna biblioteka: Proekt plianu” (“Literary Library: Draft Plan”); and “Biblioteka suchasnoї svitovoї literatury: Prospekt” (“Library of Modern World Literature: Prospectus”). This paper discusses both the bright and the dark sides of the planning of translations of texts into the Ukrainian: the analyzed lists, simultaneously, testify to the flourishing of the translation industry in Ukraine at the turn of the 1920s and 1930s and display the Bolshevik regime’s increasing suppression of freedom of choice in translation. The discussion focuses on the contents of each list (that is, choices of authors and works) from an anthropological point of view, exploring the reflection of the literary and cultural tastes and demands of early Soviet Ukrainian society as seen in the publishing plans of leading Ukrainian experts on world literature of their time. These publishing plans were later directed and limited by Soviet censorship on the eve of the mass political purges in the USSR.